1996
DOI: 10.1093/jxb/47.12.1963
|View full text |Cite
|
Sign up to set email alerts
|

Altered Rubisco activity and amounts of a daytime tightbinding inhibitor in transgenic tobacco expressing limiting amounts of phosphoribulokinase

Abstract: Transgenic tobacco with RuBP-limited photosynthetic assimilation due to a 95% reduction in phosphoribulokinase activity, had higher specific activities of Rubisco in fresh extracts and after full activation, than in the wild type. Differences in the amounts of a daytime tight-binding inhibitor were sufficient to contribute significantly to these activity differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…During the day, considerable protection against proteolysis could be provided by Rubisco carbamoylation (which is promoted in the light by an ATP‐dependent process catalysed by Rubisco activase) and/or by substrate turnover (Table 2). In addition, intermediates in the synthesis of CA1P [43] or tight binding inhibitors of Rubisco, distinct from CA1P, present in light‐adapted leaves [14,44–46] may afford similar protection under conditions in which Rubisco activity is not saturated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the day, considerable protection against proteolysis could be provided by Rubisco carbamoylation (which is promoted in the light by an ATP‐dependent process catalysed by Rubisco activase) and/or by substrate turnover (Table 2). In addition, intermediates in the synthesis of CA1P [43] or tight binding inhibitors of Rubisco, distinct from CA1P, present in light‐adapted leaves [14,44–46] may afford similar protection under conditions in which Rubisco activity is not saturated.…”
Section: Discussionmentioning
confidence: 99%
“…We are acquiring new data which show that naturally occurring Rubisco inhibitors, present in illuminated leaves [14,44,45], may protect Rubisco from stress‐induced inactivation ([52] and S. Khan, P. J. Andralojc & M. A. J. Parry, unpublished data). Hence, the protection conferred on Rubisco by CA1P may be one aspect of a more general type of protective strategy in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibitor is subsequently degraded by a light-dependent phosphatase (7). In a similar pattern, Rubisco can also accumulate inhibitors during the day through the formation of inhibitory compounds during catalysis that remain bound to the active site and hinder catalysis (8,9). These inhibitors include pentodiulose-P 2 and xylulose-P 2 , and the in vitro formation of these compounds has been well characterized (10 -18).…”
Section: Rubiscomentioning
confidence: 99%
“…Transgenic plants with altered amounts of ribulose-1, 5-bisphosphate carboxylase-oxygenase (Rubisco, EC 4.1.1.39) revolutionized the analysis of photosynthesis and its interaction with the whole plant (Stitt and Schulze 1994;Quick et al 1991b). However, the content of Rubisco accounts for 15% to 35% of total leaf N in C 3 species, and a decrease in the amount of Rubisco substantially disrupts the N balance of the plant, making it difficult to establish direct links between photosynthesis and growth and allocation (Woodrow and Berry 1988;Paul et al 1996). The study of phosphoribulokinase (PRK, EC3.1.3.11) has found that only 94% decrease in PRK activity by antisense RNA in transgenic tobacco diminishes photosynthesis at low N level (Banks et al 1999;Habash et al 1996).…”
Section: Introductionmentioning
confidence: 99%